Effect of Oxidizing Slag on Cleanliness of IF Steel during Ladle Holding Process. Issue 9 (23rd December 2014) - Qin, Yiming; Wang, Xinhua; Li, Linping; Huang, Fuxiang
Abstract The effect of oxidizing slag on cleanliness of IF steel produced by ShouGang during ladle holding process was investigated by comparing the differences of slag composition, steel composition and inclusion morphology between two processes of different slag oxidability(Process‐A < Process‐B). The results showed that, the reoxidation of slag to steel was observed during holding process, and Process‐A with the lower slag oxidability was more helpful to improve the cleanliness of molten steel during holding process by comparing the T.O of the two processes. Due to the slag reoxidation during holding process, the large petal shaped and dendritic Al2O3 inclusions generated for Process‐A, and both the numbers of Al2O3 and Al2O3‐TixO inclusions increased significantly for Process‐B. In order to slow down reoxidation rate and improve the ability of slag to absorb inclusions, (FeO) content should be reduced and (CaO)/(Al2O3) should be increased in the case of liquid slag. In conclusion, whether prolonging ladle holding time should depend on (FeO) content, (CaO)/(Al2O3) etc. parameters of slag and initial T.O of molten steel.